Heterogeneous Lead Phosphate Nucleation at Organic–Water Interfaces: Implications for Lead Immobilization - Chong Dai; Juntao Zhao; Daniel E. Giammar; Pasteris, Jill D.; Zuo, Xiaobing; Yandi* Hu (ACS Earth and Space Chemistry, 2018)
Phosphate is added to Pb-contaminated soils to induce lead immobilization through lead phosphate precipitation. Organic coatings on soils, which may affect heterogeneous lead phosphate nucleation, can impact the effectiveness of lead immobilization. Here, SiO2 surfaces were coated with silanol self-assembled thin films terminated with −COOH and −OH functional groups to act as model organic coatings on soil particles. Using grazing incidence small-angle X-ray scattering (GISAXS), heterogeneous lead phosphate nucleation on coatings was measured from mixed Pb(NO3)2 and Na2HPO4/NaH2PO4 solutions at pH 7 with varied ionic strengths (IS = 0.58, 4, and 11 mM). Raman spectroscopy identified the homogeneous precipitates in solution as hydroxylpyromorphite (Pb5(PO4)3OH). The smallest lead phosphate nuclei (4.5 ± 0.5 nm) were observed on −COOH coatings, which resulted from the highest level of lead and phosphate ion adsorption on −COOH coatings. The IS of the solution also affected the sizes of the heterogeneous precipitates on −COOH coating, with smaller nuclei (1.3 ± 0.4 nm) forming under higher IS (4 and 11 mM). This study provided new findings that can improve our understanding of lead immobilization in contaminated soil environments.